PENGEMBANGAN LEMBAR KERJA PESERTA DIDIK BERBASIS ETNOMATEMATIKA BANJAR MATERI SEGIEMPAT DAN SEGITIGA - Norhaliza Norhaliza; Rahmatya Nurmeidina; Soraya Djamilah (Universitas Muhammadiyah Lampung, 2022)
This research aims to explain the development process, validity, and practicality of student worksheets containing Banjar ethnomathematics on quadrilateral and triangle material. This type of research is development research, using the Plomp model, which consists of five phases: the initial investigation phase, the design phase, the realization/construction phase, the test phase, the evaluation, and the revision phase, and implementation phase. However, this development only reached the test, evaluation, and revision phases. The research instrument is a validation sheet and a practicality sheet. Three validators assessed aspects of validity 1 lecturer who is experienced in research linking culture and mathematics learning tools, 1 lecturer in geometry courses, and 1 mathematics teacher. The practical element was evaluated by 26 students and one teacher studying this material. The validation results from the validator obtained an index value of 0.77, which is included in the